Constitutional democratic state of India: A critique - Bhambhri, C.P. (1994)
"Taking a close critical look at the present Indian State, the author first analyses the main constitutional provisions which justify calling it a modern constitutional democratic State and then discusses its afflictions. He also analyses several factors that weaken the State before drawing his conclusion regarding growing policisation of Indian State"
Keywords: Democracy - India; Democracy